Climate Village Based On Mitigation And Adaptation With Tri Hita Karana Philosophy In Banyuasri Village - Bayu Ananta Surya, I Putu; Wetu Dinatha, Gede Rendy; Mahadewi Saraswati, Desak Putu (Institut Manajemen Wiyata Indonesia, 2024)
Banyuasri Village is located in Buleleng District, Buleleng Regency, Bali Province, Indonesia, which has an area of 1.45 km2 and is located 15 meters above sea level. The population of Banyuasri Village is 10,704 with the majority earning their living as traders, and civil servants. According to the Secretary of the Banyuasri Village, I Made Sujana Dibya S.E, he explained that rubbish and waste are crucial problems for Banyuasri Village. The increasing risk of natural disasters is felt by the community. The solution that can be proposed by the Ormawa Working and Reasoning Group of the Undiksha Technical and Vocational Faculty at the 2023 Ormawa PPK is through a climate village program based on adaptation and mitigation. The implementation method is that all PPK members are allowed to make program suggestions and take responsibility for the work they hold (participatory). Reference to the significance criteria for conformity with government programs, namely PPN 6/PN6/PP2/KP1/RKP2023 in the RAKER 2023 book, Directorate of Environmental Criminal Law Enforcement and Forestry. From the results obtained, the IKP category achieved 81% significance (SS), the dominance of the most on-target targets was pro-p 4 (67%), pro-p 2 (14%), pro-p 3 (10%), pro- p 1(9%). This is by the observations of the 2023 Bali climatology station's dry season forecast bulletin update. The northern part of the Banyuasri sub-district market is at ZOM 418 (beginning of the second dry season on April 11-20 with a rainfall value of less than 85% with a peak in June.